2015
DOI: 10.1175/jpo-d-14-0171.1
|View full text |Cite
|
Sign up to set email alerts
|

The Deep Equatorial Ocean Circulation in Wind-Forced Numerical Solutions

Abstract: propagating mostly downward, consistent with observations. We demonstrate that both types of currents arise from the rectification of DEIV, consistent with previous theories. We also find that the EDJs contribute to maintaining the EICs, suggesting that the nonlinear energy transfer is more complex than previously thought. In Solution 2, the DEC is unrealistically weak and less spatially coherent than in the first simulation probably because of its weaker DEIV. Using intermediate solutions, we find that the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
80
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 41 publications
(103 citation statements)
references
References 53 publications
11
80
2
Order By: Relevance
“…In fact Claus et al (2016) have diagnosed the forcing for the deep jets from the mooring data at 23 • W on the equator and find that the implied power input that maintains the deep jets takes place over the whole depth range occupied by the jets. Concerning the vertical phase propagation of the jets, we note that in the particular case studied by D' Orgeville et al (2007), the vertical phase propagation is not in agreement with observations, although it should be noted that their model runs are shorter than those considered by Ascani et al (2015) and Matthießen et al (2015) and possibly do not show fully developed EDJ cycles. In D 'Orgeville et al (2007), the phase propagation is such as to take energy away from the depths where the imposed destabilizing Yanai waves have relatively large amplitude to depths where the destabilizing Yanai waves have relatively low amplitude (see Fig.…”
Section: Introductioncontrasting
confidence: 62%
See 4 more Smart Citations
“…In fact Claus et al (2016) have diagnosed the forcing for the deep jets from the mooring data at 23 • W on the equator and find that the implied power input that maintains the deep jets takes place over the whole depth range occupied by the jets. Concerning the vertical phase propagation of the jets, we note that in the particular case studied by D' Orgeville et al (2007), the vertical phase propagation is not in agreement with observations, although it should be noted that their model runs are shorter than those considered by Ascani et al (2015) and Matthießen et al (2015) and possibly do not show fully developed EDJ cycles. In D 'Orgeville et al (2007), the phase propagation is such as to take energy away from the depths where the imposed destabilizing Yanai waves have relatively large amplitude to depths where the destabilizing Yanai waves have relatively low amplitude (see Fig.…”
Section: Introductioncontrasting
confidence: 62%
“…Indeed, basin modes appear to be important for describing not only the EDJs in the equatorial Atlantic Ocean but also the semi-annual and annual cycles . Ascani et al (2015) also noted that in their nonlinear model the EDJs are well represented by the gravest basin mode for a high baroclinic vertical normal mode. Furthermore, Matthießen et al (2015) showed that in their idealised model experiments, most of the energy associated with the zonal velocity along the equator has both a time scale and vertical structure associated with resonant basin modes.…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations